2014
DOI: 10.2166/ws.2014.044
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of three drinking water treatment plants using flow cytometry

Abstract: A 4-month sampling campaign has been conducted for the monitoring of three drinking water treatment plants using flow cytometry and culture-based methods to provide information related to changes in bacterial concentration according to treatments. Flow cytometry is a fast and user-friendly technique enabling bacteria quantification and viability assessment in less than 1 hour. Specific profiles regarding log-reduction of total bacteria were obtained for each treatment plant. Chlorination appeared to be the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…FCM is a fast, accurate, quantitative and reproducible technique for counting the total number of bacteria when a general nucleic acid stain is used (Hammes et al, 2008;Wang et al, 2010;Prest et al, 2013) or the number of viable bacteria when combined with viability stains (Berney et al, 2008;Helmi et al, 2014b).…”
Section: Fcm Cell Concentrations As An Alternative To Hpcmentioning
confidence: 99%
See 4 more Smart Citations
“…FCM is a fast, accurate, quantitative and reproducible technique for counting the total number of bacteria when a general nucleic acid stain is used (Hammes et al, 2008;Wang et al, 2010;Prest et al, 2013) or the number of viable bacteria when combined with viability stains (Berney et al, 2008;Helmi et al, 2014b).…”
Section: Fcm Cell Concentrations As An Alternative To Hpcmentioning
confidence: 99%
“…Monitoring treatment processes: FCM was used to characterise drinking water treatment processes in a large number of studies (e.g., Hoefel et al, 2005aHoefel et al, , 2005bHammes et al, 2008Hammes et al, , 2010bHo et al, 2012;Vital et al, 2012;Lautenschlager et al, 2014;Helmi et al, 2014b;Example S2). In studies by Hammes et al In that study, HPC data showed no difference between the different treatment options.…”
Section: Fcm Provides Relevant Quantitative Process Informationmentioning
confidence: 99%
See 3 more Smart Citations